Comparative effects of hepatocyte growth factor and tacrolimus on acute liver allograft early tolerance - Chen, Quanyu; Yang, Zhiqing; Lin, Heng; Lai, Jiejuan; Hu, Deyu; Yan, Min; Wu, Zhifang; Liu, Wei; Li, Zhehai; He, Yu; Sun, Zhe; Shuai, Ling; et al. (Frontiers in Immunology, 2023)
Allostimulated CD8+ T cells (aCD8+ T cells), as the main mediators of acute liver rejection (ARJ), are hyposensitive to apoptosis due to the inactivation of death receptor FAS-mediated pathways and fail to allow tolerance induction, eventually leading to acute graft rejection. Although tacrolimus (FK506), the most commonly used immunosuppressant (IS) in the clinic, allows tolerance induction, its use is limited because its target immune cells are unknown and it is associated with increased incidences of malignancy, infection, and nephrotoxicity, which substantially impact long-term liver transplantation (LTx) outcomes. The dark agouti (DA)-to-Lewis rat LTx model is a well-known ARJ model and was hence chosen for the present study. We show that both hepatocyte growth factor (HGF) (cHGF, containing the main form of promoting HGF production) and recombinant HGF (h-rHGF) exert immunoregulatory effects mainly on allogeneic aCD8+ T cell suppression through FAS-mediated apoptotic pathways by inhibiting cMet to FAS antagonism and Fas trimerization, leading to acute tolerance induction. We also showed that such inhibition can be abrogated by treatment with neutralizing antibodies against cMet (HGF-only receptor). In contrast, we did not observe these effects in rats treated with FK506. However, we observed that the effect of anti-rejection by FK506 was mainly on allostimulated CD4+ T cell (aCD4+ T cell) suppression and regulatory T cell (Treg) promotion, in contrast to the mechanism of HGF. In addition, the protective mechanism of HGF in FK506-mediated nephrotoxicity was addressed. Therefore, HGF as a tolerance inducer, whether used in combination with FK506 or as monotherapy, may have good clinical value. Additional roles of these T-cell subpopulations in other biological systems and studies in these fields will also be meaningful.